Development of Video Tutorials as A Media for Learning Graphic Design in Vocational High Schools - Nugraha, Ridho Aprilia; Iskandar, M. Yakub (JERIT: Journal of Educational Research and Innovation Technology, 2024)
Education will not be separated from technological developments which are utilized in developing learning media for children. Tutorial videos have an important role in supporting the learning process in class. Teachers predominantly use whiteboard media so that students find it difficult to understand the material presented because the learning process is still teacher cantered. The need for appropriate learning media such as video tutorials makes the learning process student cantered. The research aims to develop valid and practical video tutorial learning media. The research method is R&D (Research and Development) by Borg and Gall this model stage was modified into 5 steps, namely initial product development planning, product validation, limited trials and final product. The material validity results were 4.53 in the "Very Valid" category. The validity of media 1 and 2 received a value of 4.83 and 4.60 in the "Very Valid" category. The results of the practicality test by 15 students obtained a score of 4.79 in the "Very Practical" category. Video tutorials can be used by students and teachers during the learning process in class.